The Novelty of the Language of the Quran and the Diversity of Opinions of Philologists - Mammadov, Nasrulla (Scholarya Demo Journal of Ruby, 2022)
The article discusses the novelty of the language of the Quran and the diversity of opinions of philologists on this issue. It is noted that the Arabs, who have demonstrated high eloquence within the style they have been accustomed to and managed to create beautiful poetic images for centuries, lost themselves when faced with the expression and unusual style of the Quran and could not hide their admiration in front of the wonderfulness of the word of God. This new word art pattern, with Arabic letters and Arabic words, differed from all existing word art patterns in terms of its expression style, harmony between words, meaning within meaning, and finally, the use of new compositions and constructions. All such facts continued to surprise the Arab lexicographers and poets who went far ahead of the neighboring nations in eloquence and oratory.